An Augmented Reality-Based Interactive Flipbook to Foster Conceptual Change in Learning Chemical Reaction Rates - Ananda Oktaviani; Aldi Firman Syahputra; Diah Ayu Apriliasari; Moh Threewahyu Saifulloh; Eva Ayu Safitri; Kusumawati Dwiningsih (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Misconceptions about chemical reaction rates often persist because the topic involves abstract processes that are difficult to visualize through conventional instruction. This study developed and evaluated an Augmented Reality (AR) based interactive flipbook for reaction rate learning, focusing on validity, practicality, and initial effectiveness in reducing misconceptions and supporting conceptual change. Research and Development (R and D) was conducted using a modified 4D model limited to the define, design, and develop stages. Content and construct validity were assessed by chemistry education experts, learning media experts, and chemistry teachers. Practicality was examined through student response questionnaires and observations of learning activities. Effectiveness was measured using a three tier diagnostic test, with pretest and posttest results analyzed using the Wilcoxon test and effect size. Expert evaluation indicated that the flipbook met validity criteria, with mode scores of at least 4 across all assessed aspects. Practicality outcomes were high, reflected by a 90.11% questionnaire score and 95.87% activity observation score. The intervention reduced average misconceptions by 55.72%, supported by a significant difference (p < 0.05) and a very large effect size (0.846). Results suggest AR integrated flipbooks can strengthen visualization of reaction rate concepts and facilitate conceptual change by directly targeting common misconceptions. Further studies with broader implementation are recommended to strengthen generalizability.